Antimicrobial Activity of Selected Philippine Marine Sponges - Oclarit, Jose; Pocsidio, Glorina; Raymundo, Asuncion (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The extracts of the eleven species of fresh and dried marine sponges belonging to eight families under Class Demospongia were tested for their antimicrobial activity. The test microorganisms used were: Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis, Candida utilis and Aspergillus niger. Ten species (Adocia sp., Pellin asp., Cribrochalina sp., Xestospongia sp., Trachyopsis sp., Halichondria sp., Phyllospongia foliascens, both juvenile and mature Biemna fortis and Plakortis sp.) demonstrated varied antimicrobial activity depending on the state of the material and on the solvent used. Extracts from fresh sponge samples gave greater inhibition compared with extracts from dried ones. Alcohol solvent showed greater efficiency in extracting active components from fresh sponges while methanol toluene solvent was efficient in dried sponges. For all ten species, inhibition was found to be greater against Gram-positive bacteria but Adocia sp., Pellina sp., Cribcrochalina sp., Trachyopsis sp., Suberites sp., and Phyllospongia foliascens inhibited fungi. The Mycale sp. did not show any antimicrobial activity.